Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Intersex Initiative: From "Intersex" to "DSD" - Koyama, Emi (2006)
keynote speech presented at Translating Identity conference held at University of Vermont in February 2006.
Keywords: EDI; LGBTQIA2+; approches et analyses; capacitisme; cours; discipline; intersexuation; patriarcat; premier cycle; queer; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

Handicap, recherche et changement social. L’émergence du paradigme émancipatoire dans l’étude de l’exclusion sociale des personnes handicapées - Boucher, Normand (Lien social et Politiques, 2003)
Le champ du handicap a subi de profondes transformations au cours des quatre dernières décennies dans la majorité des sociétés postindustrielles. Ce phénomène, qui influence les approches théoriques et la recherche à l’intérieur des sciences sociales, a fait surgir un nouveau paradigme émancipatoire basé sur une remise en cause des rapports entre le chercheur et le « sujet d’étude ». Dans cet article, nous explorons le développement de ce paradigme en nous appuyant sur l’expérience britannique, et nous discutons de son apport à la compréhension du handicap et des politiques sociales en abordant la question du rôle et de la position des acteurs au sein de la pratique de recherche
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; EDI; approches et analyses; capacitisme; corps; cours; discipline; histoire et politique; premier cycle; périodes historiques; ressource en ligne; ré; santé; sciences humaines; sex1920; sociologie; systèmes d'oppressions; thématiques; études critiques du handicap

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires